KONFLIK CINA-PRIBUMI DAN DAMPAKNYA BAGI PERTUMBUHAN INDUSTRI BATIK DI TRUSMI 1948 - Mahdun Mahdun (Jurnal Tamaddun : Jurnal Sejarah dan Kebudayaan Islam, 2017)
In the history of Indonesia, the period 1930 to 1950 is a very crucial period. The people of Indonesia are experiencing the events that have great impact in the future. The incident started with an explosion of economic recession and ended with a very eagerly awaited independence by the people of Indonesia. The phenomenon made Indonesian people more sentimental towards foreign ethnic groups, including to Chinese. Many horrific events occurred during that time, the expulsion, burning and killing of the Chinese people, and one of them occurred in Trusmi Village Cirebon in 1948. It certainly had an impact on the development of Trusmi batik industry. This study uses historical method (historical study) by using descriptive-analysis method as a set of procedures. From this study it is known that the situation of Trusmi society before the conflict between the Chinese and the indigenous people both in the social and religious and socio-economic sides initially went well, but after the incident it caused the Chinese to be isolated from the social life of society in general. Nevertheless, the terrible event is a gateway for indigenous people to stand independently in running the industry Batik.Keywords: conflict, China, indigenous, implications, and Trusmi